Fe doped TiO2 thin films for Solar Cell Applications - Ahmed N Abd, M. A. Ahmed, Nadir Fadhil Habubi, Ayad F. Alkaim (International Journal of Advanced Science and Technology, 2020)
Titanium dioxide and TiO2:1%Fe thin ﬁlms thermal evaporation on optical glass and p-type silicon substrates at room temperature under vacuum. Transmittance Over 95% ​​was noticed in NIR region. the energy gap values were (3.6- 3.5 eV) for the grown films. XRD data offer that these films were polycrystalline with hexagonal wurtzite structure. From (I-V) characteristics of TiO2/p-Si it is noticed that short circuit current (Isc) is 49 mA, open circuit voltage (Voc) is 45 V, Imax is 37 mA, and Vmax is 33 V, the efficiency (ɳ) have been calculated to be 6%, The high conversion efficiency (η) was 7% for 1% Fe-doped TiO2/p-Si device.